Mountain Masculinity: The Life and Writing of Nello "Tex" Vernon-Wood in the Canadian Rockies, 1906-1938 - Andrew Gow (Athabasca University Press, 2008)
In 1906, Nello Vernon-Wood (1882-1978) reinvented himself as Tex Wood, Banff hunting guide and writer of "yarns of the wilderness by a competent outdoorsman." His homespun stories of a vanishing world, in such periodicals as The Sportsman, Hunting and Fishing, and the Canadian Alpine Journal, have much to tell us about the west as envisioned by those who wanted to leave the early 20th century behind-or at least read about others who had done so. In the writings of his persona " Tex," Vernon-Wood created an image of the frontier that blended the West of his guiding experiences with the West as a literary object. Editors Gow and Rak, for their part, guide the reader with a framing introduction to the work, as well as to each article.